(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
In this article, according to the linguistic theory, the concept of speech is explained by understanding the attitude of the speaker through a certain intonation tone, what tasks this tone can perform in a sentence, and its role in speech.